Pengembangan Permainan Monopoli Sebagai Media Pada Materi Puisi Kelas IV SDN 105352 Pasar Miring Kecamatan Pagar Merbau - Yesi Wulandari; Syarifah Ainun Harahap; Nuri Ramadhan (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
This development research aims to explain the procedures for developing monopoly game media and analyze student responses to monopoly game media. The development of monopoly game media was carried out to foster students' enthusiasm for learning in poetry material. Apart from that, this media was developed in accordance with the characteristics of students and the students' learning environment, namely the school environment implements a teaching and learning process through collaboration between subject matter and the natural environment, so that the learning process is done while learning. play. This research includes Research and Development research using the ADDIE (Analize, Design, Develop, Implement, Evaluate) development model which was tested on 30 class IV students at SDN 105352 Pasar Miring, Pagar Merbau District. Data collection techniques in this research used questionnaires, interviews, observation and documentation. Data analysis techniques use quantitative data analysis and qualitative data analysis. This monopoly game media was developed as a learning medium for poetry material for class IV Indonesian language subjects at SDN 105352 Pasar Miring, Pagar Merbau District. This monopoly game media product has several components, namely a container, game board, manual and answer key, icon cards, dice and player miniatures. This research and development produces monopoly game learning media products. The validation results for the monopoly game media product obtained valid criteria with a score from the material expert validator of 97.5%, the media design expert validator 87.5%, the learning expert validator 95%. The monopoly game media also received a positive score from student responses, namely 97.5%. Based on the student response criteria, the monopoly game media as a medium for learning poetry material in Indonesian subjects is positive.